A Copper-Based Biosensor for Dual-Mode Glucose Detection - Li, Kai; Xu, Xiaoyu; Liu, Wanshan; Yang, Shouzhi; Huang, Lin; Tang, Shuai; Zhang, Ziyue; Wang, Yuning; Chen, Fangmin; Qian, Kun (Frontiers in Chemistry, 2022)
Glucose is a source of energy for daily activities of the human body and is regarded as a clinical biomarker, due to the abnormal glucose level in the blood leading to many endocrine metabolic diseases. Thus, it is indispensable to develop simple, accurate, and sensitive methods for glucose detection. However, the current methods mainly depend on natural enzymes, which are unstable, hard to prepare, and expensive, limiting the extensively applications in clinics. Herein, we propose a dual-mode Cu2O nanoparticles (NPs) based biosensor for glucose analysis based on colorimetric assay and laser desorption/ionization mass spectrometry (LDI MS). Cu2O NPs exhibited excellent peroxidase-like activity and served as a matrix for LDI MS analysis, achieving visual and accurate quantitative analysis of glucose in serum. Our proposed method possesses promising application values in clinical disease diagnostics and monitoring.